2020
DOI: 10.1298/ptr.e9982
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Activities-specific Balance Confidence scale-Japanese (ABC-J) in community-dwelling stroke survivors

Abstract: Objective: In Japan, there were 1.17 million people with stroke in 2014; however, studies on community rehabilitation among stroke survivors are lacking. The Activities-specific Balance Confidence (ABC) scale is used in many languages to evaluate patients undergoing stroke rehabilitation. This study aimed to investigate the reliability and validity of the Japanese ABC scale (ABC-J) version among patients ! 6 months after stroke. Methods: This cross-sectional study was conducted with 88 post-stroke patients (me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Clinical outcome measures: Scores on clinical measures such as the ABC scale, the Mini-BESTest, BBS, and treadmill natural walking speed were analyzed to determine the effect of treadmill-based gait-slip training. The ABC scale, a 16-item self-reported scale assessing balance confidence during the performance of activities without loss of balance have been known to be valid and reliable among community-dwelling PwCS [ 57 , 58 , 59 ]. The Mini-BEST test, a 14-item test including reactive balance control and anticipatory adjustments, is a valid and reliable tool to measure dynamic balance in PwCS [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…Clinical outcome measures: Scores on clinical measures such as the ABC scale, the Mini-BESTest, BBS, and treadmill natural walking speed were analyzed to determine the effect of treadmill-based gait-slip training. The ABC scale, a 16-item self-reported scale assessing balance confidence during the performance of activities without loss of balance have been known to be valid and reliable among community-dwelling PwCS [ 57 , 58 , 59 ]. The Mini-BEST test, a 14-item test including reactive balance control and anticipatory adjustments, is a valid and reliable tool to measure dynamic balance in PwCS [ 60 , 61 ].…”
Section: Methodsmentioning
confidence: 99%
“…We obtained the data from a previous multicenter, cross-sectional observational study, which cross-culturally validated the ABC-J 16-item scale (Ishige, Wakui, Miyazawa, and Naito, 2020). In that study, the sample size required to estimate reproducibility was 50 based on an intra-class correlation coefficient (ICC2,1) target value of 0.8 and a 95% confidence interval (CI) of ±0.1 (Giraudeau and Mary, 2001).…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…Among several balance self-efficacy measures that are patient-reported outcome measures (PROMs), the Activities-specific Balance Confidence Scale (ABC scale) is widely used in the clinical and research areas of post-stroke rehabilitation and is positioned as an important outcome in PA intervention studies (Tang et al, 2015) and can be a modifiable factor for various important outcomes such as improving balance, mobility, activities of daily living (ADL), quality of life, reduced depression (Botner, Miller, and Eng, 2005;Forsberg and Nilsagard, 2013;Ishige, Wakui, Miyazawa, and Naito, 2020;Korpershoek, van der Bijl, and Hafsteinsdottir, 2011;Salbach et al, 2006), and post-stroke PA (Thilarajah et al, 2018). The ABC scale is recommended by the American Physical Therapy Association as a rehabilitation PROM for patients at subacute and chronic post-stroke stages (Sullivan et al, 2013) and is selected as one of the core outcome measures (Moore et al, 2018) according to the recent Clinical Practice Guideline for adults with neurologic conditions undergoing rehabilitation by the Academy of Neurologic Physical Therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This score has been used and validated in various populations and has been translated to numerous languages. [19][20][21][22][23] Miller et al 24 have shown evidence of validity for the ABC in older adults with LLA.…”
Section: Abcmentioning
confidence: 99%